Effects of maternal exposure to procymidone on hepatic metabolism in the offspring of mice. Issue 4 (3rd January 2023) - Wang, Xiaofang; Hu, Lingyu; Jin, Cuiyuan; Qian, Mingrong; Jin, Yuanxiang
Abstract: As an effective fungicide widely used in agricultural production, the excessive procymidone (PRO) residue has been detected in the environment and food. Our previous study demonstrated that PRO could destroy the intestinal barrier in mice and has a joint toxic effect. To explore the cross‐generational impact of maternal exposure, 10‐week‐old C57BL/6 female mice were orally administrated to 10 and 100 mg/kg body weight/day of PRO during pregnancy and lactation. The offspring obtained nutrients from the maternal through the placenta and breast milk, and PRO residues were detected in the liver, intestine, and feces of F1 generation. Fecal examination found that the residual PRO had been completely metabolized when the offspring mice grew to 35 days. The drug residue of F1 generation male mice was higher than that of female mice. We attributed this result to the difference in cytochrome P450 (CYP450) enzyme expression between male and female mice. The transcriptional levels of CYP1A1, CYP1A2, CYP2D9, and CYP3A4, and CYP450 protein expression levels, were higher in female mice. Furthermore, targeted MS of plasma revealed abnormal amino acid levels. In addition, PRO‐induced hepatic metabolite changes in F0 and F1‐7w mice. KEGG pathway analysis further showed that PRO jointly changed the amino acid biosynthesis pathway of the maternal and offspring. In summary, these results indicated that maternal exposure to PRO during a special period would interfere with self metabolism, and offspring will also have metabolic disorders.